Effect of Blending Parameters on Physical Properties of Styrene-Butadiene Rubber Coagulum Modified Asphalt Binder - Syazana; Nurul Hidayah binti Mohd Kamaruddin (Recent Trends in Civil Engineering and Built Environment, 2021)
Polymer modified asphalt binder have gained high interest in recent years due to its promising performance. However, the uses of natural polymer such as natural latex is susceptible to contamination and require certain treatment to reduce the water content. This issue can cause the low homogeneity with asphalt binder. Therefore, this study explored another type of synthetic polymer, Styrene-Butadiene Rubber (SBR) coagulum. The base binder of penetration grade 60/70 was blended with 5% of SBR coagulum to determine the suitable blending temperature and blending time. Then this modified binder was further testing for physical properties; penetration and ductility test. The results showed the penetration value decreased with increasing blending temperature and time. The suitable blending temperature and time were found as 190C and 120 minutes. For conclusion, the application of using SBR coagulum as modifier has a good potential as asphalt binder modifier.